2022
DOI: 10.1111/ajt.16893
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of survival after lung transplantation in telomerase-related gene mutation carriers: A retrospective cohort

Abstract: Carriers of germline telomerase‐related gene (TRG) mutations can show poor prognosis, with an increase in common hematological complications after lung transplantation (LT) for pulmonary fibrosis. The aim of this study was to describe the outcomes after LT in recipients carrying a germline TRG mutation and to identify the predictors of survival. In a multicenter cohort of LT patients, we retrospectively reviewed those carrying pathogenic TRG variations (n = 38; TERT, n = 23, TERC, n = 9, RTEL1, n = 6) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…36,37 However, the mean overall survival is >5 years after lung transplantation in the absence of myelodysplasia before lung transplantation. 38,39 We observed only one death in the six patients who underwent lung transplantation, with a median follow-up of 21 months, and none showed myelodysplasia or liver cirrhosis.…”
Section: Discussionmentioning
confidence: 86%
“…36,37 However, the mean overall survival is >5 years after lung transplantation in the absence of myelodysplasia before lung transplantation. 38,39 We observed only one death in the six patients who underwent lung transplantation, with a median follow-up of 21 months, and none showed myelodysplasia or liver cirrhosis.…”
Section: Discussionmentioning
confidence: 86%
“…Individuals with other ILDs and shortened TL and/or telomerase mutations have been shown to have more rapid progression, 6 shorter transplant-free survival, 9 and worse transplant-related outcomes. 10 It will be important to determine if RA-ILD individuals with short PBL-TL have similarly poor outcomes, as measurement of PBL-TL could be an important tool in guiding treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced telomere length has also been associated with a shorter time to onset of chronic lung allograft dysfunction (CLAD) 34 . However, a recent study 35 found no difference in the overall post‐LT median survival between the groups with (3.75 years) and without (3.0 years) TRG mutation. Univariate analysis showed the diagnosis of myelodysplasia and a reduced telomere length before LT in TRG mutation carriers were the only factors significantly associated with overall survival, suggesting that LT is hazardous but might be offered to TRG mutation carriers after careful immune‐haematological evaluation.…”
Section: Discussionmentioning
confidence: 99%